2012
DOI: 10.1093/carcin/bgs290
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer action of garcinol in vitro and in vivo is in part mediated through inhibition of STAT-3 signaling

Abstract: Garcinol, obtained from Garcinia indica, has exhibited some promising anticancer activity. In particular, our earlier work has demonstrated its ability to inhibit cell proliferation and induction of apoptosis in multiple cancer cell lines representative of breast, prostate, as well as pancreatic cancers. However, its exact mechanism of action remains largely unclear. Here we show that garcinol also targets signal transducer and activator of transcription-3 (STAT-3) signaling pathway. STAT-3 is frequently found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 40 publications
1
47
0
3
Order By: Relevance
“…Our results are consistent with a recent report in which garcinol was found to suppress the activation of STAT3 in breast, prostate, and pancreatic cancer cell lines (15), although the detailed molecular mechanisms underlying its STAT3 inhibitory effects were not elucidated in this study. Also, STAT3 phosphorylation plays a pivotal role in proliferation and survival of tumor cells (42).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results are consistent with a recent report in which garcinol was found to suppress the activation of STAT3 in breast, prostate, and pancreatic cancer cell lines (15), although the detailed molecular mechanisms underlying its STAT3 inhibitory effects were not elucidated in this study. Also, STAT3 phosphorylation plays a pivotal role in proliferation and survival of tumor cells (42).…”
Section: Discussionsupporting
confidence: 91%
“…Garcinol has gained much attention in the field of cancer research in recent years, and several reports have shown the antineoplastic and chemopreventive role of garcinol in different cancers, such as leukemia, colorectal, gastrointestinal, and breast cancers (12)(13)(14)(15)(16). Although there is a prior evidence showing that garcinol can inhibit 4-nitroquinoloine 1-oxide-induced tongue carcinogenesis (17), mechanisms through which garcinol elicits its antitumor activity, specifically in HNSCC, is unknown till date.…”
Section: Introductionmentioning
confidence: 99%
“…Literature revealed that garcinol exhibited antioxidant, antiinflammatory, anticancer and hepatoprotective activities [6][7][8][9] . Garcinol was also reported to exhibit radical scavenging activity and suppressed protein glycation in vitro [5] .…”
Section: Garcinol Is a Polyisoprenylated Benzophenone Derivative Isolmentioning
confidence: 99%
“…Garcinol interferes with multiple signaling cascades to induce apoptosis in several cancer cell lines. The known mechanisms of action of garcinol in apoptosis involve the inactivation of the signal transducer and activator of transcription 3 (STAT-3), NFκB and phosphoinositide 3-kinase (PI3K)/serine/ threonine-specific protein kinase (Akt) signaling pathways [31,38,44]. This inactivation increases the expression of pro-apoptotic gene products (Bax, Bak) over pro-survival gene products (Bcl-xL, Bcl-2, Mcl-1, survivin), the release of cytochrome c into the cytosol, the activation of caspase-3, and thus, the induction of apoptosis [51].…”
Section: Anti-cancer Activitiesmentioning
confidence: 99%